Workshop on disruptive information and communication technologies for innovation and digital transformation - Leitão, Paulo (Ed.) (2019)
The workshop on Disruptive Information and Communication Technologies for Innovation and Digital transformation, organized under the scope of the DISRUPTIVE project (disruptive.usal.es) and held on December 20, 2019 in Bragança, aims to discuss problems, challenges and benefits of using disruptive digital technologies, namely Internet of Things, Big data, cloud computing, multi-agent systems, machine learning, virtual and augmented reality, and collaborative robotics, to support the on-going digital transformation in society. The main topics included: • Intelligent Manufacturing Systems • Industry 4.0 and digital transformation • Internet of Things • Cyber-security • Collaborative and intelligent robotics • Multi-Agent Systems • Industrial Cyber-Physical Systems • Virtualization and digital twins • Predictive maintenance • Virtual and augmented reality • Big Data and advanced data analytics • Edge and cloud computing • Digital Transformation The workshop program included 16 accepted technical papers, 2 invited talks and 1 technical demonstration of use cases. This volume contains six of the papers presented at the Workshop on Disruptive Information and Communication Technologies for Innovation and Digital Transformation.